2014
DOI: 10.1111/ijcp.12365
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interdisciplinary treatment on physical and psychosocial parameters in patients with fibromyalgia: results of a randomised trial

Abstract: An interdisciplinary intervention may be appropriate for patients referred to a hospital pain management unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 48 publications
0
24
0
Order By: Relevance
“…Amongst the studies, two compared the combined intervention with waitlist control [26,35] and three with usual care [29,33,34]. One study compared the combined intervention with pharmacological therapy as treatment as usual [32]. Fourteen studies compared it to physical exercise alone [1925,27,28,30,31,33,35,36], whereas only three used CBT alone [25,33,35] as a comparison group for the combined intervention.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Amongst the studies, two compared the combined intervention with waitlist control [26,35] and three with usual care [29,33,34]. One study compared the combined intervention with pharmacological therapy as treatment as usual [32]. Fourteen studies compared it to physical exercise alone [1925,27,28,30,31,33,35,36], whereas only three used CBT alone [25,33,35] as a comparison group for the combined intervention.…”
Section: Resultsmentioning
confidence: 99%
“…One study [34] used patients’ diaries to score pain intensity but did not describe the scoring method. After excluding this study, a total of 12 studies reported follow-up outcomes on pain intensity [2027,29,31,32,36], although not all reported post-intervention outcomes at the same time. Note that one of these studies [21] was listed as having 1-year follow-up outcomes, but in fact the CBT component of the combined intervention continued on a monthly basis after the conclusion of the main intervention; this needs to be taken into consideration when interpreting the results.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations